Genotyping of relapsing polychondritis identified novel susceptibility HLA alleles and distinct genetic characteristics from other rheumatic diseases. (30th May 2016) - Terao, Chikashi; Yoshifuji, Hajime; Yamano, Yoshihisa; Kojima, Hiroto; Yurugi, Kimiko; Miura, Yasuo; Maekawa, Taira; Handa, Hiroshi; Ohmura, Koichiro; Saji, Hiroh; Mimori, Tsuneyo; Matsuda, Fumihiko
Abstract: Objective. To uncover the genetic background of relapsing polychondritis (RPC), a rare autoimmune disease with unknown mechanisms characterized by systemic inflammation of the cartilage, to deepen our understanding of the pathophysiology of RPC and show its distinct genetic characteristics from other rheumatic diseases. Methods. A total of 102 patients with RPC and 1000 healthy subjects were recruited for a two-staged genetic association study and genotyped for six HLA classical loci. Haplotype association tests were also performed. The associations of amino acid (AA) residues and positions with susceptibility to RPC were analysed. Frequencies of representative susceptibility HLA alleles to other rheumatic diseases in RPC were also analysed. Results. HLA-DRB1*16:02, HLA-DQB1*05:02 and HLA-B*67:01, which are in linkage disequilibrium with each other, were associated with RPC (P = 1.9 × 10 −6, 1.4 × 10 −5 and 0.00024, respectively). AA residue at position 57 in HLA-DQB1, the most significant position in type I diabetes mellitus, showed the strongest association among AA residues. HLA-DR4, a known susceptibility allele in Germans, showed a trend of susceptibility association without significance (P = 0.067). No associations were observed between the three alleles and clinical phenotypes. Representative susceptibility HLA alleles to RA, SLE, Behçet disease and Takayasu arteritis did not show enrichment in RPC in spite of sufficient statistical power. Conclusions. HLA-DRB1*16:02, HLA-DQB1*05:02 and HLA-B*67:01, in linkage disequilibrium with each other, are associated with susceptibility to RPC Importance of HLA-class II loci in RPC susceptibility is suggested. RPC is considered a genetically distinct disease from other rheumatic diseases.